The travel advice as an inhibiting factor of tourist movement - Mylonopoulos Dimitrios; Moira Polyxeni; Kikilia Aikaterina (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
Tourism is significantly affected by unpredictable and uncertain factors such as the occurrence of a terrorist attack, an epidemic outbreak or a natural disaster, etc. The impact of these phenomena on the tourist movement of the country or the place where the event occurred is aggravated by the way it is presented by the media both locally and internationally. The adverse climate gets worse by the issuance of travel advice that usually accompanies such phenomena and has the effect of limiting or even halting tourist flows. In order to identify and study the different types of travel advice that have been issued during international tourism crisis incidents, an internet search was carried out using keywords. Moreover, a study on the travel advice issued by major tourists' origin states, as the USA, Australia, Canada, Germany, the United Kingdom, etc. was carried out. Incidents (terrorist attacks, epidemics, natural disasters) which had a great impact on tourism were then selected. In addition, the issuance of travel advice, their different issuing authorities, the classification level and the impact on the tourism of the country or the place in question were examined. An analysis of the reaction and the instructions of major international organizations (World Health Organization, World Tourism Organization) concerning the management of such crises, directly or indirectly affecting tourism, were also analyzed. The study of the relevant websites, the international literature and the recorded incidents shows that the issuing of travel advice has negative effects on many sectors of tourism activity and is a bottleneck for tourism development. In fact, in many cases, travel advice is used by countries to exert pressure on other countries in order to achieve a desired result. Due to the enormous economic and social effects when issuing travel advice, the states proper management is necessary in order to minimize the negative consequences and avoid obstructing the free movement of tourists, as provided for in international treaties and declarations. As no systematic research on the impact of travel advice on a country and the degree of influence depending on the issuing entity (state, international organization or private entity) has been carried out so far, further investigation of the issue is suggested, by performing research, both on travelers and travel organizations on the effects of issuing travel advice.